Erythropoietin Promotes Deleterious Cardiovascular Effects and Mortality Risk in a Rat Model of Chronic Sports Doping - Piloto, Nuno (2015)
Athletes who abuse recombinant human erythropoietin (rhEPO) consider only the benefit to performance and usually ignore the potential short and long-term liabilities. Elevated haematocrit and dehydratation associated with intense exercise may reveal undetected cardiovascular risk, but the mechanisms underlying it remain to be fully explained. This study aimed to evaluate the cardiovascular effects of rhEPO in rats under chronic aerobic exercise. A ten week protocol was performed in four male Wistar rat groups: control-sedentary; rhEPO-50 IU kg(-1), 3 times/wk; exercised (EX)-swimming for 1 h, 3 times/wk; EX + rhEPO. One rat of the EX + rhEPO group suffered a sudden death episode during the week 8. rhEPO in trained rats promoted erythrocyte count increase, hypertension, heart hypertrophy, sympathetic and serotonergic overactivation. The suddenly died rat's tissues presented brain with vascular congestion; left ventricular hypertrophy, together with a "cardiac-liver", suggesting the hypothesis of heart failure as cause of sudden death. In conclusion, rhEPO doping in rats under chronic exercise promotes not only the expected RBC count increment, suggesting hyperviscosity, but also other serious deleterious cardiovascular and thromboembolic modifications, including mortality risk, which might be known and assumed by all sports authorities, including athletes and their physicians.